Effect of Titanium Carbide Particles on Mechanical Properties of Aluminum Matrix Composites - Zaman Khalil Ibrahim (Wasit Journal of Engineering Sciences)
In this research aluminum matrix composites (AMCs) was reinforced by titanium carbide (TiC) particles and was produced. Powder metallurgy technique (PM) has been used to fabricate AMCs reinforced with various amounts (0%, 4%, 8%, 12%, 16% and 20% volume fraction) of TiC particles to study the effect of different volume fractions on mechanical properties of the Al-TiC composites. Measurements of compression strength and hardness showed that mechanical properties of composites increased with an increase in volume fraction of TiC Particles. Al-20 % vol. TiC composites exhibited the best properties with hardness value (97HRB) and compression strength value (275Mpa).